‘LAWGIC’: An Application for Automated Legal Document Classification and Retrieval - Thambi, Adarsh S; Devangavi, Arpitha; R, Pankaja; Joshi, Aditi (Journal of Electronics and Informatics, 2024)
This research proposes LAWGIC (where law meets logic), an automated legal document classification and retrieval system leveraging topic modelling using Latent Dirichlet Allocation (LDA). LAWGIC utilizes the Indian Kanoon website as its data source, focusing on Supreme Court of India documents. LDA is used to extract meaningful themes from legal documents and assign them to the most relevant topic. This frees legal professionals from manual categorization, improves accuracy, and empowers them to work with greater efficiency. The system also provides a user interface for efficient retrieval and exploration of documents and topics.
Keywords: Automated Document Categorization; Information Retrieval; Legal; Latent Dirichlet Allocation (LDA); Topic Modelling